2014
DOI: 10.1007/s11306-014-0682-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrimetabolomics fingerprinting to identify biomarkers of bread exposure in a free-living population from the PREDIMED study cohort

Abstract: Bread is one of the most widely consumed foods. Its impact on human health is currently of special interest for researchers. We aimed to identify biomarkers of bread consumption by applying a nutrimetabolomic approach to a free-living population. An untargeted HPLC-q-TOF-MS and multivariate analysis was applied to human urine from 155 subjects stratified by habitual bread consumption in three groups: non-consumers of bread (NCB, n=56), white-bread consumers (WHB, n=48) and whole-grain bread consumers (WGB, n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
0
34
1
Order By: Relevance
“…8b), despite the reports that glycine conjugated and unconjugated bile acids may be responsible for the discrimination between venous and arterial plasma samples after WG wheat intake in pigs49. Similarly, the lignan metabolite, enterolactone glucuronide ( 26 ), has been reported as a biomarker to distinguish WG rye consumption from RG group39. However, our data showed that the urinary excretion of enterolactone glucuronide in the WG group is not significantly different from the RG group (Table 2 and Fig.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…8b), despite the reports that glycine conjugated and unconjugated bile acids may be responsible for the discrimination between venous and arterial plasma samples after WG wheat intake in pigs49. Similarly, the lignan metabolite, enterolactone glucuronide ( 26 ), has been reported as a biomarker to distinguish WG rye consumption from RG group39. However, our data showed that the urinary excretion of enterolactone glucuronide in the WG group is not significantly different from the RG group (Table 2 and Fig.…”
Section: Resultscontrasting
confidence: 64%
“…1) were attributed to wheat phytochemicals ARs and BXs3839. Other altered compounds linked to WG consumption are phenolic acids and related metabolites, such as ferulic acid (FA) sulfate, 1,2,3-benzenetriol sulfates degraded from gallic acid40, 3-methoxycatechol sulfate derived probably from 3-methylgallic acid40, 3-methylcatechol41, and 4-acetylphenol42 (Table 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these findings demonstrate that there are several results on combining biomarkers in a model, although it is important to find the simplest combination of metabolites that can produce a proper effective outcome (Xia et al, 2013). The development of robust food biomarkers has important goals aimed at providing better classification of individuals in terms of dietary exposure (Garcia-Aloy et al, 2014), and in turn this would improve assessment of the relationship between diet and chronic disease (O'Gorman et al, 2013).…”
Section: Biomarkers Associated With Wine Exposure and Classificationmentioning
confidence: 99%
“…Upon intake, these compounds were subject to different transformations, primarily N ‐dehydroxylation, deglycosylation, glucuronidation, and sulfation, in addition to direct absorption and transformation into hydroxylated phenylacetamide derivatives and AP sulfate . Recent metabolomic analysis of urine of a very large clinical study in free‐living men and women found various BX‐derived compounds as a biomarker of habitual bread consumption even in the group with habitual white‐bread consumptions . This indicated that bread consumers around the globe are exposed to BXs to a certain degree even if they do not consume rye or wholegrain wheat, which are known to contain high amounts of BXs.…”
Section: Introductionmentioning
confidence: 99%